THE EFFECT OF USE OF E-COMMERCE AND THE EXISTENCE OF E-WALLET FACILITIES ON CONSUMPTIVE BEHAVIOR IN THE MILENIAL GENERATION IN JAKARTA - Ghia Syifa Almukhlisah; Harya Kuncara Wiralaga; Dicky Iranto (Transpublika Publisher, 2023)
This study aims to determine the effect of using e-commerce and using e-wallets on the consumptive behavior of the millennial generation in Jakarta. The method used in this research is a quantitative method. The reachable population in this study is the millennial generation in Jakarta as many as 100 people. Sampling technique with Purposive Sampling, with data collection using a questionnaire. The data analysis technique used in this research is using the primary data of the regression model. The results of this study indicate that: 1) Use of E-Commerce has a positive and significant effect of 6,032 on Consumptive Behavior, 2) Use of E-Wallet has a positive and significant effect of 7,962 on Consumptive Behavior, 3) Use of E-Commerce and Use of E-Wallet simultaneously have a positive and significant effect of 70,6% and the rest are influenced by other factors.